ANALISIS FAKTOR BUDAYA ORGANISASI,KOMPENSASI,DAN KEMPETENSI TERHADAP KOMITMEN ORGANISASIONAL DI PT PEGADAIAN CABANG PONCOL - Rokhmad Budiyono; Fidyah Yuli Ernawati; Ita Monica (Sekolah Tinggi Ilmu Ekonomi Semarang, 2022)
The right HRM is the key to success in achieving an organizational goal. The existence of HRM in an organization aims to increase the contribution of employees in the organization. One of the successes of HRM is determined in growing employee organizational commitment. How far the organizational commitment of employees to the organization will greatly determine the achievement of organizational goals. This study aims to determine whether there is an influence between organizational culture, compensation, and competence on organizational commitment at PT. Poncol Branch Pawnshop. The population in this study were all employees of PT. Pegadaian Branch Poncol, with a sample of 35 respondents. The variables in this study are organizational culture, compensation, and competence as independent variables and organizational commitment as the dependent variable. The sampling technique was carried out by the saturated sampling method (Census). The data used is primary data obtained from the distribution of questionnaires and the analytical method used is multiple linear regression analysis. The results of the first hypothesis stated